Understanding context environment, language, and information architecture - Hinton, Andrew (O'Reilly Media, 2015)
This practical, insightful book provides a powerful toolset to help information architects, UX professionals, and web and app designers understand and solve the many challenges of contextual ambiguity in the products and services they create. Find out how to make better sense of cross-channel, multi-device products or services. Discover how language creates infrastructure in organizations, software, and the Internet of Things. Learn models for figuring out the contextual angles of any user experience.